Characterization of performance of conformal microstrip antennas - Anaekwe, Ikenna Valentine (2013)
The conformity of microstrip antennas has interested so many because of its ability to function normally whether it remains flat or transformed geometrically to the shape of the surface on which they are mounted upon. An obvious benefit is the increase in their inconspicuousness. At the same time their performances have been known to change. Recently these changes have been studies to realize any potential for positively exploiting them to achieve various design goals. This thesis is an intensive study of the behavior of conformal microstrip antennas when adapted to circular and elliptical curvatures on either of the two (2) geometric planes of an antenna. A scheme is employed to deal with the potential ambiguity of having to mention different antenna dimensions and curvature dimensions when trying to generalize results. Two (2) terms are been used to make simpler the vast amount of results: ?circumferential coverage? instead of simply ?curvature radius? (that is rather specific in influence to a specific antenna dimension), and ?eccentricities? instead of ?semi-axes? (for describing different elliptical curvatures). A total of eight (8) different antenna arrays operating at different frequency bands (902 ? 928MHz, 2.400 ? 2.484GHz, and 5.725 ?5.850GHz) are studied. The chosen frequency bands are to realize functional antenna models with very different dimensions. The thesis then provides information on the effects of curvature on the different performance parameters of the different antennas including the resonant frequency, return loss, impedance bandwidth, directivity, radiation and overall efficiency, beam width, and side-lobe level. All of the works therein have been conducted in CST Microwave Studio.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Antennas -- Design & construction; Microstrip antennas